Self-congruence theory: Factors affecting brand loyalty in fast-moving consumer goods industry - Nurul Aini; Augusty Ferdinand (Jurnal Inovasi Ekonomi, 2021)
This study aims to formulate a conceptual model for analyzing several variables on customer engagement and brand loyalty, especially in the fast-moving consumer goods (FMCG) industry. The self-congruence theory used in this study will go through the value of congruity, brand attractiveness, and customer-brand identification. The study uses structural equation modeling with samples of 105 respondents. The result is value congruence has a positive effect on brand attractiveness and customer brand identification. Customer engagement has a positive impact on customer brand identification. Brand attractiveness has a positive impact on customer brand identification and brand loyalty. Also, customer brand identification has a positive effect on brand loyalty.